The new blues: Determining significant factors in right-wing populist support among young Canadians. - Lara Choy (The Young Researcher)
The recent popularity of figures such as Pierre Poilievre and events such as the Ottawa “Freedom Convoy” demonstrate the rise of right-wing populism among young Canadian voters. Through a mixed-methods approach with thematic analysis, this study attempted to determine the most significant factors contributing to right-wing populist support in this demographic. The survey of 56 self-identified conservative Canadian university students and Reddit users aged 18–35 found that right-wing populist support was predicated on three factors: economic uncertainty, with unsustainably high cost of living and mismanaged fiscal policies; distrust in government, with negative perceptions of institutions, including the media; and cultural conflict, with backlash against “woke” ideas and “non-traditional” values. The themes point to disillusionment with Canada’s current economic, political, and social environment, and a desire for the alternative messaging often found in right-wing populism. The findings contain significant implications regarding current and upcoming Canadian voter behaviour and the effects of populist worldviews.